The Crime of Murder of Parents and Families in the Reform of Indonesian Criminal Law - I Gusti Agung Kiddy Krsna Zulkarnain; Eko Soponyono (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2022)
This study aims to describe and analyze the regulation of the crime of murder of parents and families in Indonesian criminal law today and in the future. This study uses a normative legal research method with the statute approach, the conceptual approach and the comparative approach. The results of this study, firstly, the crime of murder of parents and families, is not explicitly regulated in the current Indonesian criminal law. The formulation of the offense of murder in the current Criminal Code (Article 338 and Article 340) is only aimed at taking the lives of others without distinguishing who is the object/target. Second,The formulation of the September 2019 New Criminal Code Concept has accommodated the concept of criminal law reform with a value-oriented approach, related to the inclusion of cultural values of respect, appreciation and protection of the dignity of parents and families as embodied in Article 464 paragraph (2). In this article, it has been distinguished who is the object/target of the crime of murder and it is also used as a reason for the aggravation of the crime. Until now, the New Criminal Code has not been ratified. Criminal law reform will not run optimally, if it has not been taken with a policy approach. The existence of the Bulgarian Criminal Code and the French Criminal Code can also be used as benchmarks or legal comparisons, thus enriching the formulation of the crime of murder of parents and families in the New Criminal Code Concept in the future.